Human capital effects of marriage payments - Siwan Anderson (IZA World of Labor, 2014)
Payments at the time of marriage, which are ubiquitous in developing countries, can be substantial enough to impoverish parents. Brideprice and dowry have both been linked to domestic violence against women, and inflation in these payments has prompted legislation against them in several jurisdictions. Marriage payments are often a substitute for investment in female human capital, so from a welfare and policy perspective, they should be prohibited. This highlights the importance of promoting direct economic returns over legal and customary rights.
Keywords: J12; J16; J18; D10; 330; marriage; brideprice; dowry